2017
DOI: 10.1007/s00455-017-9792-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Esophageal Acidification on Troublesome Symptoms: An Approach to Characterize True Acid GERD in Dysphagic Neonates

Abstract: Objective To quantify and compare maximal extent (height) of acid reflux events (AREs) on symptom generation in dysphagic neonates. Methods Dysphagic neonates (N=53), born at 30 ± 5.3 wks gestation, underwent 24-hour pH-impedance study for the evaluation of troublesome symptoms purported to be due to gastroesophageal reflux disease (GERD). AREs (pH < 4 for > 4 seconds) detected by impedance (Z) were categorized by maximal extent as refluxate reaching distal (Z6, Z5), middle (Z4, Z3), or proximal (Z2, Z1) imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 63 publications
2
50
1
Order By: Relevance
“…This finding confirms our initial hypothesis that, in some subjects with particular characteristics of reflux, there is a significant association between CR and GER events. This agrees with an earlier study by Sivalingam et al, which showed that CR events were associated with proximal GER events in subjects with pathological reflux index …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This finding confirms our initial hypothesis that, in some subjects with particular characteristics of reflux, there is a significant association between CR and GER events. This agrees with an earlier study by Sivalingam et al, which showed that CR events were associated with proximal GER events in subjects with pathological reflux index …”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that in our study, we observed an almost double reflux index in the positive SAP group confirming the hypothesis that a pathological reflux index could be associated with an increased esophageal sensitization responsible for a greater likelihood to develop CR symptoms as a consequence of reflux …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations